Understanding the Influence of ESG Pillars on Financial Returns and Firm Value: The sequel of Theory and Empirical evidence - Dr Yousaf Khan,; Muhammad Usman,; Junaid ul Hassan,; Iqra Bashir Student,; Muhammad Tariq, (Dialogue Social Science Review (DSSR), 2024)
This study investigates the impact of Environmental, Social, and Governance (ESG) pillars on financial returns and firm value among non-financial firms listed on the Pakistan Stock Exchange (PSX), using Stakeholder Theory as a framework. The study focuses on the top 100 non-financial PSX firms between 2014 and 2023, employing a purposive sampling approach. Data is sourced from PSX, NBP, and other reputable platforms. Various statistical models, including Pooled OLS, Random Effects, and Fixed Effects, are used, with the Fixed Effects Model found to be the most reliable for the analysis. The analysis reveals a positive, statistically significant relationship between ESG pillars and both financial returns (ROE) and firm value (Tobin’s Q). Firms with stronger ESG practices tend to experience higher ROE and Tobin’s Q. Control variables like firm size and sales growth also positively impact financial returns and Firm Value, while financial leverage has no significant effect. The sample is limited to the top 100 non-financial PSX firms, which may limit the generalizability of the findings. This study is one of the first to empirically explore the impact of ESG pillars on financial performance (ROE) and firm value (Tobin’s Q) in Pakistan. The findings provide productive insights for investors, corporate managers, policymakers, and other stakeholders in Pakistan, highlighting the importance of ESG practices for improving financial returns and firm value.